Overview of toroidal momentum transport - Peeters, A; Angioni, C; Bortolon, A; Camenen, Y; Casson, F; Duval, B; Fiederspiel, L; Hornsby, W; Idomura, Y; Hein, T; Kluy, N; Mantica, P; et al. (2011)
Toroidal momentum transport mechanisms are reviewed and put in a broader perspective. The generation of a finite momentum flux is closely related to the breaking of symmetry (parity) along the field. The symmetry argument allows for the systematic identification of possible transport mechanisms. Those that appear to lowest order in the normalized Larmor radius (the diagonal part, Coriolis pinch, E × B shearing, particle flux, and up-down asymmetric equilibria) are reasonably well understood. At higher order, expected to be of importance in the plasma edge, the theory is still under development. © 2011 IAEA, Vienna.